Evaluation of the Correlation Between Vitamin D3 Serum Level, Age, gender and BMI in Rheumatoid arthritis Patients in Al- Kut City/Iraq - Ameerah M. Zarzoor1, Wafaa Sahib Hamza2, Zaidon T. Al-aqbi3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Rheumatoid arthritis (RA) is an auto-immune disease a chronic characterized leading to joint loss (RA) disease affects nearly 1% of the world. This study is aimed to determine the effect of age, gender and vitamin D level on the efficacy of RA. One hundred and twenty patients (twenty male and one hundred female) with RA in this study were divided, into groups according to their age. Vitamin D levels were measured in the serum using the enzyme-linked immunosorbent assay (ELISA) blood test. Assessment of the relationship between disease severity and average level of vitamin D was examined by the scale of scores in different groups with rheumatoid arthritis. At p<0.05, significant levels of the above tests have been detected. The current study indicates there is a significant relationship between overweight high underweight below (18.5) BMI and age rate (26-36) patients with RA with deficiency of vitamin D level in serum. The results showed a highly significant difference between patients’ gender groups in as compared disease severity, female more than male with RA disease.